Kinetic Study of Aluminum Sulphate and Ammonium Aluminum Sulphate Coagulants in Wastewater Treatment (JOURNAL OF ADVANCES IN CHEMISTRY, 2007)
An investigation into the kinetics of two inorganic coagulant namely: aluminum sulphate octadecahydrate (Al2(SO4)3.18H2O) an ammonium aluminum sulphate dodecahydrate (NH4Al(SO4)2.12H2O) was studied to determine the effect of certain kinetic parameters on coagulation performance of the above mentioned coagulants. Results of analysis obtained revealed that the rate constant (k) for Al2(SO4)3.18H2O was 5.727s-1, while that for NH4Al(SO4)2.12H2O was 2.282s-1. However, the order of the reaction (xn) of Al2(SO4)3.18H2O and NH4Al(SO4)2.12H2O with the wastewater was 1.0 and 1.0, respectively, indicating that both reactions were first order. Considering the mechanism of the reaction, the general trend observed indicated that the Al2(SO4)3.18H2O reaction was thrice as fast as the NH4Al(SO4)2.12H2O reaction. This fact together with the larger value of k for Al2(SO4)3.18H2O obtained in the experiment lend credence to the widely held believe that Al2(SO4)3.18H2O is a more effective coagulant than NH4Al(SO4)2.12H2O in wastewater treatment.